Testing for financial-led, export-led and import-led growth hypotheses on four Asian emerging economies - Tan, Siow Hooi; Habibullah, Muzafar Shah; Mohamed, Azali; Baharumshah, Ahmad Zubaidi (Faculty of Economics and Management, Universiti Putra Malaysia, 2007)
The main objective of this study is to investigate the dynamic relationships between economic growth and macroeconomic variables, namely financial deepening, exports and investment for the cases of Singapore, South Korea, Taiwan and Thailand. The vector errorcorrection model (VECM) is employed to distinguish between shortrun and long-run causal effects in examining the three led-growth determinants. The out-of-sample dynamics of the system are also picked up through variance decomposition analysis. The empirical results suggest that financial deepening leads to economic growth in South Korea, Singapore and Thailand. In terms of exports, the findings demonstrate that export-led growth hypothesis is supported for all four Asian economies, namely Singapore, South Korea, Taiwan and Thailand. Apart from export promotion strategies and financial liberalisation, the evidence also shows that economic growth in these four Asian economies is found to be generated by capital formation or investment.